Optical Estimation on Pollution Level of Respirable Dust Based on Infrared Transmitting Behavior in Coalmine Fully Mechanized Working Face - Wen-Zheng Wang; Yan-Ming Wang; Guo-Qing Shi (Journal of Spectroscopy)
Respirable coal particle generated during underground mining is the main cause for gas-dust explosions and coal workers’ pneumoconiosis (CWP) which needs accurate monitoring especially on its concentration. Focusing on the coal dust pollution in the fully mechanized working face of Huangbaici coalmine, coal particle was sampled for further industrial analysis and FT-IR test to obtain its chemical composition and optical constant. Combined with the simulated spatial distribution of airborne dust, the spectral transmission characteristics of coal dust within wavelengths of 2.5 to 25 μm under different operating conditions were obtained. The simulation results show that the transmittance and aerosol optical depth (AOD) of coal dust are closely linked and obviously influenced by the variation of dust generation source (intensity of dust release, position of coal cutting, and the wetting of the coal seam) and airflow field (wind speed and direction of ventilation). Furthermore, an optical channel of 1260–1280 cm−1 (7.937–7.813 μm) which is almost only sensitive to the variation of dust concentration but dull to the diameter change of coal dust was selected to establish the correlation of dust concentration and infrared transmittance. The fitting curve was then applied to retrieve the equivalent dust concentration based on optical information, and the comparison results demonstrate that the estimated pollution level is consistent with field measurement data in engineering practice.